Eric Voegelin and the problem of Christian political order - Herndon, Jeffrey C., 1962- (Eric Voegelin Institute series in political philosophy., 2007)
"Analyzes the development of Voegelin's thought regarding the origins of Christianity in the person of Jesus, the development of the church in the works of Paul, and the relationship between an immanent institutional order symbolizing the divine presence and the struggle for social and political order"--Provided by publisher.